More sophisticated than a drink cooler or an old sphygmomanometer but still not adequate for prehospital blood: A market review of commercially available equipment for prehospital blood transport and administration. Issue Volume 61:Issue S1 (2021)Supplement (16th July 2021) - Martin, Silver M.; Fisher, Andrew D.; Meledeo, Michael A.; Wampler, David; Nicholson, Susannah E.; Raczek, Katherine; April, Michael D.; Weymouth, Wells L.; Bynum, James; Schauer, Steven G.
Abstract: Background: Hemorrhage is the leading cause of death in trauma patients with most fatalities occurring before reaching a higher level of care—this applies to both the civilian setting and the military combat setting. Hemostatic resuscitation with increased emphasis on blood transfusion while limiting use of crystalloids has become routine in trauma care. However, the prehospital setting—especially in combat—presents unique challenges with regard to storage, transport, and administration. We sought to evaluate available technology on the market for storage and administration technology that is relevant to the prehospital setting. Study design and methods: We conducted a market review of available technology through subject–matter expert inquiry, reviews of published literature, reviews of Federal Drug Administration databases, internal military publications, and searches of Google. Results: We reviewed and described a total of 103 blood transporters, 22 infusers, and 6 warmers. Conclusions: The risk of on‐scene fatality in trauma patients and recent developments in trauma care demonstrate the need for prehospital transfusion. These transfusions have been logistically prohibited in many operations. We have reviewed the current commercially available equipment and recommended pursuit of equipment that improves accessibility to field transfusion. Current technology has limited applicability for the prehospital setting and is further limited for the military setting.